Psychedelics Road Ahead: Are We Ready? - Mahesh R Gowda (Indian Journal of Private Psychiatry)
Psychedelics are classed as a schedule I substance under the Controlled Substances Act of 1970 because of the potential for mind-changing effects. In vulnerable people, unsupervised use has the potential to lead to suicide. However, the management of end-of-life anxiety, severe resistant depression, resistant obsessive–compulsive disorder, and substance abuse is met with a high failure rate. The preliminary study on psychedelics has yielded promising results, prompting the Food and Drug Administration (FDA) to classify them as a breakthrough medicine. More phase 3 research, funded by pharmaceutical company, are in the works. Similar studies should be funded by national institutes and government bodies to ensure unbiased results, as the findings of such studies may need legislative changes.